ANALISIS PENGARUH KUALITAS PELAYANAN DAN KEPUASAN PENGGUNA JASA TRANSPORTASI ONLINE GOJEK DAN GRAB DI KOTA BATAM MENGGUNAKAN ALGORITMA K-MEANS - Firawani; Pintubipar, Saut (LPPM Universitas Putera Batam, 2023)
In this era of economic development, many activities are carried out easily by today's society, especially in the field of transportation. With advances in the field of information technology such as the internet, it can affect various aspects of human life. So that companies that provide online transportation services are competing to provide services and facilities for their users. Because user satisfaction greatly affects the success or failure of a company. One of them is the Grab and Gojek companies. They are competing to improve services in the application for the satisfaction of the people who use it. In this last project, the author is interested in conducting research on customer satisfaction using data mining techniques, namely K-Means clustering algorithm and linear regression simplicity. This method can help the author in grouping the effect of Service Quality on Service User Satisfaction and enthusiasts of Gojek Grab Online Transportation in Batam City which is in the Batam City sub-district based on data from community respondents on the distribution of questionnaires that have been carried out by the author. In the final results there will be 5 categories, namely strongly disagree, disagree, neutral, agree, and strongly agree.